Food Insecurity as a Predictor of Hurricane Exposure among Underserved Adolescents - Katherine R. Arlinghaus; Daphne C. Hernandez; Craig Johnston (New Prairie Press, 2019)
Low-income populations are at increased risk for experiencing negative hurricane exposures and food insecurity. However, little is known regarding how pre-hurricane food insecurity experiences are related to youth hurricane exposure. This study examined the types of hurricane disaster exposures low-income, ethnic minority adolescents experienced during Hurricane Harvey and examined the association between food insecurity and hurricane exposure. Low-income adolescents (n = 185) were recruited from a Houston-area school district. Two days before the hurricane, food insecurity was assessed. Adolescents with at least one affirmative answer on the 9-item USDA Child Food Security Survey Module were classified as food insecure. Adolescents self-reported hurricane exposure three weeks post-hurricane using both the National Child Traumatic Stress Network Hurricane and Assessment Referral Tool and Survey of Hurricane Katrina Evacuees. Affirmative answers to lacking access to food, water, or medicine, being rescued, home damage, and displacement were each given a score of one and summed to create an overall hurricane exposure score. A covariate-adjusted linear regression model regressed overall hurricane exposure onto food insecurity. Separate covariate-adjusted logistic regression models were performed where each individual hurricane exposure was regressed onto food insecurity. Prior to the hurricane, 46% of adolescents experienced food insecurity and 43% experienced hurricane exposure. Pre-hurricane food insecurity (p = 0.004) and being foreign born (p = 0.033) were associated with increased hurricane exposure. Adolescents who experienced food insecurity had 132% higher odds of lacking access to fresh water (p = 0.047) and 105% higher odds of lacking access to food (p = 0.034) during the hurricane. Food insecurity and immigrant status appear to be at-risk indicators for hurricane exposure. Schools serving underserved adolescents could consider assessing food security and immigration status as part of disaster preparedness programs.